The Efficacy of Mesenchymal Stem Cell Therapies in Rodent Models of Multiple Sclerosis: An Updated Systematic Review and Meta-Analysis - He, Jialin; Huang, Yan; Liu, Jianyang; Lan, Ziwei; Tang, Xiangqi; Hu, Zhiping (Frontiers in Immunology, 2021)
Studies have demonstrated the potential of mesenchymal stem cells (MSCs) administration to promote functional recovery in preclinical studies of multiple sclerosis (MS), the effects of MSCs on remyelination are poorly understood. We wished to evaluate the therapeutic effects of MSCs on functional and histopathological outcomes in MS, therefore, we undertook an updated systematic review and meta-analysis of preclinical data on MSCs therapy for MS. We searched mainstream databases from inception to July 15, 2021. Interventional studies of therapy using naïve MSCs in in vivo rodent models of MS were included. From each study, the clinical score was extracted as the functional outcome, and remyelination was measured as the histopathological outcome. Eighty-eight studies published from 2005 to 2021 met the inclusion criteria. Our results revealed an overall positive effect of MSCs on the functional outcome with a standardized mean difference (SMD) of -1.99 (95% confidence interval (CI): -2.32, -1.65; P = 0.000). MSCs promoted remyelination by an SMD of -2.31 (95% CI: -2.84, -1.79; P = 0.000). Significant heterogeneity among studies was observed. Altogether, our meta-analysis indicated that MSCs administration improved functional recovery and promoted remyelination prominently in rodent models of MS.